Pneumonia Severity Assessment: CURB-65 versus PSI in Predicting Admission Need and Mortality — A Prospective Comparative Study (Academia Journal of Medicine, 2026)
Background: Community-acquired pneumonia (CAP) remains a leading cause of morbidity and mortality worldwide. Accurate severity assessment is crucial for determining appropriate disposition and treatment intensity. The CURB-65 and Pneumonia Severity Index (PSI) are widely utilized scoring systems, yet their comparative performance in diverse clinical settings continues to be debated. Methods: A prospective cohort study was conducted at two teaching hospitals over 24 months, enrolling 634 adult patients with confirmed CAP. Both CURB-65 and PSI scores were calculated at presentation. Primary outcomes included requirement for hospital admission and 30-day all-cause mortality. Receiver operating characteristic (ROC) curve analysis and comparative statistics were performed. Results: The mean age was 62.7 ± 18.4 years, with 56.8% male patients. Hospital admission was required in 412 patients (65.0%), and 30-day mortality occurred in 58 patients (9.1%). For mortality prediction, PSI demonstrated an AUC of 0.842 (95% CI: 0.798– 0.886) compared to 0.814 (95% CI: 0.766–0.862) for CURB-65 (p=0.089). For predicting admission need, PSI showed superior discrimination (AUC 0.812 vs. 0.758, p=0.012). PSI risk class IV-V had 87.9% sensitivity and 72.4% specificity for mortality, while CURB-65 ≥3 showed 79.3% sensitivity and 78.6% specificity. Conclusion: Both scoring systems demonstrate good predictive accuracy for mortality in CAP patients. PSI shows superior performance for determining admission need, while CURB-65 offers comparable mortality prediction with greater simplicity. Clinical context should guide score selection.
Keywords: community-acquired pneumonia; CURB-65; Pneumonia Severity Index; mortality prediction; hospital admission; severity assessment; prognostic scoring